Robot-assisted laparoscopic orchiopexy: A comparative analysis with laparoscopic orchiopexy - Rensing, Adam J.; Qadar, Abdul; Higganbotham, Clark; Frimberger, Dominic; Meenakshi-Sundaram, Bhalaajee (Frontiers in Urology, 2023)
Background While undescended testes are relatively common, the nonpalpable testis remains a challenging problem. The gold standard treatment remains the laparoscopic orchiopexy. However, today robot-assisted surgery has challenged traditional laparoscopy in many areas of urology. Yet the value of this new approach remains controversial, given concerns with operative time and cost. We reviewed our contemporary results of both robot-assisted orchiopexy (RALO) and traditional laparoscopic orchiopexy (TLO). Our primary aims were to retrospectively compare success rates, and operative time. Our secondary aims were to compare costs and complications related to each method. Methods In this study, all patients treated with laparoscopic and robot-assisted laparoscopic orchiopexy from April 2017 to January 2022 were reviewed using CPT code 54692. Exclusion criteria included bilateral concomitant orchiopexy or concomitant “major surgery,” or follow up less than 6 months. Also excluded were 1st stage orchiopexies. For the purposes of comparison, 1-stage and 2nd stage orchiopexies were included in the analysis. Patient demographics, surgical operative notes and documentation were all reviewed. Results After exclusion criteria was applied, 16 and 17 remained in the laparoscopic and robot-assisted cohorts, respectively. Upon follow up, all patients in both the laparoscopic and robot-assisted cohorts were noted to have a healthy testicle palpable in the dependent portion of the scrotum. The median operative time in the TLO group was 71 minutes, compared to 101 minutes in the RALO group (Figure 1) (p>0.0001). When comparing median hospital charges, the TLO group was lower at $38,813, compared to $46,455 in the RALO group (Figure 2) (p = 0.0069). There was one postoperative complication in the TLO group (localized wound infection), compared to zero in the RALO group. Conclusions The robot-assisted orchiopexy is safe and effective. However, at this time it remains more costly in terms of time and resources.